The Legal Impact of the Canada-United States Free Trade Agreement on Canadian Water Exports - Dufour, Sophie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1993)
In recent years, the issue of Canadian water exports has assumed a prominent position on the policy agenda of both Canada and the United States. As water supplies in several western states of the U.S.A. have been increasingly depleted over the past three decades, the threat of a water crisis has raised interest in the possibility of diverting Canadian waters, originating presumably in the Great Lakes Basin. While the beginning of the 1980s has already witnessed a number of heated debates over Great Lakes water transfers, the signing of the Canada-United States Free Trade Agreement on the 2nd of January 1988, revives the polemic since it is viewed by some as a new menace to the future supply of Canadian waters. The present paper, which is divided in two parts, begins with an examination of a number of events which have raised significant concern about the prospect of major water transfers from the Great Lakes Basin, the latest being the conclusion of the Canada-United States Free Trade Agreement. It then analyses the legal effects of the Agreement on Canadian water resources. This study concludes that there is nothing in the deal to suggest that Canada has in any way conceded future access to its water resources to the United States.